Odpowiedź:
[tex]a)\ \ 7\sqrt{6}-2\sqrt{6}=(7-2)\sqrt{6}=5\sqrt{6}\\\\b)\ \ \sqrt{77}\cdot\sqrt{1\frac{4}{7}}=\sqrt{77\cdot1\frac{4}{7}}=\sqrt{\not77^1^1\cdot\frac{11}{\not7_{1}}}=\sqrt{11\cdot11}=\sqrt{11^2}=11\\\\c)\ \ \sqrt{500}+7\sqrt{5}=\sqrt{100\cdot5}+7\sqrt{5}=10\sqrt{5}+7\sqrt{5}=17\sqrt{5}\\\\d)\ \ 7\sqrt{21}\cdot\frac{1}{3}\sqrt{3}=\frac{7}{3}\sqrt{21\cdot3}=\frac{7}{3}\sqrt{63}=\frac{7}{3}\sqrt{9\cdot7}=\frac{7}{\not3}\cdot\not3\sqrt{7}=7\sqrt{7}[/tex]
[tex]e)\ \ (\frac{2\sqrt{21}}{7})^2=\frac{2^2\cdot(\sqrt{21})^2}{7^2}=\frac{4\cdot21}{49}=\frac{84}{49}=\frac{12}{7}=1\frac{5}{7}[/tex]